A decline in HIV and syphilis epidemics in Chinese female sex workers (2000-2011): a systematic review and meta-analysis. - Zongxing Yang; Junwei Su; Xiaorong Peng; Nanping Wu (PLoS ONE, 2013)
BACKGROUND: Female sex workers (FSWs) play an important role in transmitting HIV and syphilis from high-risk groups to the general population. However, the trends in HIV and syphilis epidemics in Chinese FSWs in the period after 2000 are unclear to date. METHODS: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement was followed. Seven databases were searched for published peer-reviewed articles. The incidence of HIV and syphilis in FSWs in different time periods, provinces and workplaces in China were separately pooled by meta-analysis. Correlation analysis was conducted between HIV and syphilis incidence and study time, respectively. RESULTS: After 1,662 articles were screened, 190 published papers were included in the final analysis. Estimated HIV prevalence was 0.284% (95% CI: 0.080-0.488%) in the period 2000-2002, 0.211% (95% CI: 0.149-0.273%) in 2003-2005, 0.242% (95% CI: 0.190-0.294%) in 2006-2008 and 0.041% (95% CI: 0.024-0.058%) in 2009-2011. The corresponding syphilis prevalence was 9.669% (95% CI: 7.810-11.529%), 4.970% (95% CI: 4.384-5.556%), 4.404% (95% CI: 4.032-4.775%) and 3.169% (95% CI: 2.738-3.600%), respectively. Spearman rank correlation coefficients were -0.165 (p = 0.002) between HIV prevalence and study time, and -0.209 (p = 0.000) between syphilis prevalence and study time. The combined HIV prevalence was 0.318% (95% CI: 0.156-0.479%) in medium and high-tier workplaces and 0.393% (95% CI: 0.176-0.610%) in low-tier workplaces. The corresponding syphilis prevalence was 3.216% (95% CI: 2.192-4.240%) and 13.817% (95% CI: 10.589-17.044%), respectively. CONCLUSIONS: Our data suggested a decline in HIV and syphilis epidemics in FSWs in China on a national level during the study period (2000-2011). FSWs in low-tier workplaces should be given more attention in the future to ensure they are included in prevention programs for HIV and sexually transmitted diseases.